Corticotropin-releasing factor receptor signaling and modulation: implications for stress response and resilience - Vasconcelos,Mailton (2020)
Abstract Introduction In addition to their role in regulation of the hypothalamic-pituitary-adrenal-axis, corticotropin-releasing factor (CRF) and its related peptides, the urocortins, are important mediators of physiological and pathophysiological processes of the central nervous, cardiovascular, gastrointestinal, immune, endocrine, reproductive, and skin systems. Altered regulation of CRF-mediated adaptive responses to various stressful stimuli disrupts healthy function and might confer vulnerability to several disorders, including depression and anxiety. Methodology This narrative review was conducted through search and analysis of studies retrieved from online databases using a snowball method. Results This review covers aspects beginning with the discovery of CRF, CRF binding protein and their actions via interaction with CRF receptors type 1 and type 2. These are surface plasma membrane receptors, activation of which is associated with conformational changes and interaction with a variety of G-proteins and signaling pathways. We also reviewed the pharmacology and mechanisms of the receptor signaling modulatory activity of these receptors. Conclusion This review compiles and presents knowledge regarding the CRFergic system, including CRF related peptides, CRF binding protein, and CRF receptors, as well as some evidence that is potentially indicative of the biological roles of these entities in several physiological and pathophysiological processes.